2010
DOI: 10.1038/oby.2009.352
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fat–Water MRI and Single‐voxel MRS in the Assessment of Hepatic and Pancreatic Fat Fractions in Humans

Abstract: The ability to accurately and noninvasively quantify fatty infiltration in organs such as the liver and the pancreas remains a critical component in understanding the link between obesity and its comorbidities such as type 2 diabetes and fatty liver disease. Single‐voxel (1H) proton magnetic resonance spectroscopy (MRS) has long been regarded as the gold‐standard noninvasive technique for such measurements. Recent advances in three‐dimensional fat–water magnetic resonance imaging (MRI) methods have led to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
162
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(170 citation statements)
references
References 36 publications
7
162
1
Order By: Relevance
“…Our study extends the existing works by performing state-of-the-art assessment of the pancreas in a large number of subjects in the general population. Th e IDEAL-MRI allows faster and better measurements of small organs such as the pancreas ( 35 ). We not only provided important epidemiological data, but also defi ned the normal range of pancreatic fat.…”
Section: Fatty Pancreas and Insulin Resistancementioning
confidence: 99%
“…Our study extends the existing works by performing state-of-the-art assessment of the pancreas in a large number of subjects in the general population. Th e IDEAL-MRI allows faster and better measurements of small organs such as the pancreas ( 35 ). We not only provided important epidemiological data, but also defi ned the normal range of pancreatic fat.…”
Section: Fatty Pancreas and Insulin Resistancementioning
confidence: 99%
“…1, fat is distributed at a low level throughout each pancreas, and localised very high concentrations of fat are rare within the organ. One of the advantages of the three-point Dixon technique is that it is possible to study smaller organs with precise knowledge of boundaries [3]. We have previously reported that the pancreas is 30% smaller in volume and has a more serrated border in type 2 diabetes compared with age-, weight-and sex-matched controls [4].…”
mentioning
confidence: 99%
“…In this study, when IDEAL is based on a single lipid resonance, we refer to it as single-peak IDEAL (SP-IDEAL), and when it is based on multiple lipid resonances, it is referred to as multipeak IDEAL (MP-IDEAL). Even though the in vivo accuracy of IDEAL in the estimation of fat fractions has been adequately characterized for the measurement of hepatic fat fractions (16)(17)20), the in vivo accuracy of the technique for BM has not as yet been determined.…”
mentioning
confidence: 99%
“…If we assume that the fat content of hematopoietic cells is negligible in comparison to that of adipocytes, and that the water content of adipocytes is negligible compared with that of the remainder of softmarrow tissues, CF is also equivalent to 1 minus the volume fat fraction. Both MRI and proton magnetic resonance spectroscopy (H-MRS) have been used to measure fat fractions in BM (12-13) and liver (14)(15)(16)(17). Hence, it is possible to measure CF noninvasively in a patient using MRI or H-MRS.…”
mentioning
confidence: 99%